Kontrak/Akad Dalam Keuangan Syariah - Dede Abdurohman (Ecobankers : Journal of Economy and Banking, 2020)
Riba is the main enemy in sharia economics / finance, therefore all Indonesian Muslims must know what is sharia economy, how does the sharia economy work, is it in accordance with the Islamic concept of the Qur'an, Hadith, Ijma, and Qiyas, and regulations other applicable in Indonesia. This study aims to determine the contract / contract in Islamic finance. This type of research is descriptive research. The technique used to gather data through the study of literature or literature. The data processing technique is with qualitative data analysis. Islamic financial / economic contact that is someone who binds two or more people to each other in an agreement which is based on the principles of Islamic law, namely the Qur'an, Hadith, and others to meet the needs of life whether it is commercial (getting an advantage) and non-commercial (not getting a profit) directly or indirectly. There are several principles in sharia contracts, this is what distinguishes from conventional contracts. Among the principles that must exist in Islamic financial contracts are the principles of voluntary, trustful, cautious (endeavor), unchanging (luzum), equality (taswiyah), transparency, ability, ease (taisir), good faith, halal reasons. And each principle must be contained / contained in a contract / contract so that it becomes a feature of kahs in sharia financial contracts. Some sharia products make sharing of contracts in sharia contracts, and their classification into 2 contracts / agreements. Namely the Tabaru contract, which is a voluntary contract that does not benefit. Then the tijarah contract, a contract that is often used by Islamic financial institutions, because this agreement presents benefits and is permitted by Islamic law. Keywords: Contract; contract; finance Abstrak Riba menjadi musuh utama dalam ekonomi/keuangan syariah, oleh karenanya seluruh muslim indonesia harus mengetahui apa itu ekonomi syariah, bagaimana sistem kerja ekonomi syariah, apakah sudah sesuai dengan konsep Islam yakni Al-Qur’an, Hadits, Ijma, dan Qiyas, serta peraturan lainnya yang berlaku di Indonesia. Penelitian ini bertujuan untuk mengetahui kontrak/akad dalam keuangan syariah. Jenis penelitian yang digunakan adalah penelitian deskriptif. Teknik yang digunakan untuk mengumpukan datanya memalui studi literatur atau pustaka. Teknik pengolahan datanya ialah dengan analisis data kualitatif. Kontak keuangan/ekonomi syariah yaitu seseorang yang saling mengikatkan diri dua orang maupun lebih dalam suatu kesepakatan yang dilandsai berdasarkan prinsip hukum islam yakni al-qur’an, hadits, dan lain-lain untuk memenuhi kebutuhan hidup baik itu sifatnya komersil (mendapatkan suatu keuntungan) maupun non komersil (tidka mendapatkan suatu keuntungan) yang secara langsung maupun tidak langsung. Terdapat beberapa asas dalam kontrak syariah, hal ini yang membedakan dengan kontrak konvenional. Diantara asas yang harus ada dalam kontrak keuangan syariah yaitu asas sukarela, amanah, kehati-hatian (ikhtiyati), tidak berubah (luzum), kesetaraan (taswiyah), transparansi, kemampuan, kemudahan (taisir), itikad baik, sebab yang halal. Dan setiap asas harus termuat/dituangkan dalam sebuah akad/kontrak sehingga menjadi ciri kahs dalam kontrak keuangan syariah.Beberapa prodak syariah menjadikan terbaginya akad dalam kontrak syariah, dan klasifikasinya menjadi 2 akad/perjanjian. Yaitu akad tabaru, yakni akad sukarela yang tidak mendapatkan keuntungan. Kemudian akad tijarah, akad yang sering digunakan oleh lembaga keuangan syariah, karena akad ini yang menghadirkan keuntungan dan diperbolehkan secara hukum Islam. Kata Kunci: Kontrak; akad; keuangan